Planning Aisyiyah dalam Meningkatkan Ketahanan dan Keharmonisan Keluarga Pedagang Kaki Lima Di Kecamatan Medan Tembung Kota Medan - Julyanda, Fanny; Muhammad Habibi Siregar (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The author describes the planning made/designed by Aisyiyah Kecamatan Medan Tembung Medan City, namely by creating several programs that can encourage/improve the resilience and harmony of the families of street vendors. Therefore, researchers conducted Field Research using descriptive qualitative methods, using several data collection techniques in the form of observation, interviews, and documentation to obtain accurate data or information. The results that the author gets Aisyiyah provides open space for street vendors to market merchandise and help market merchandise at Aisyiyah activities. The author suggests that Aisyiyah should develop by creating workshops for street vendors and marketing them online through social media. As well as the need for government involvement to empower street vendors who can also be said to be people who are economically weak who really need care or assistance from the government so that the resilience and harmony in their families can also be intact and maintained.